Karakteristik Lokasi dan Pola Resapan: Data, Analisis dan Respon - Ichwana Ichwana; Sumono Sumono; Delvian Delvian (Rona Teknik Pertanian, 2012)
Characteristics of the Location and Recharge Pattern: Data, Analysis and ResponseABSTRACT. Infiltration as a movement of water could determine a large amount of water which could move over the soil surface to the river, and the water that went into the ground. The information of water infiltration in watershed was required to make decision about sustainable water resources. On the other hand, the infiltration was dynamic, that was why it was interesting to be analyzed. The purpose of this study was to determine differences in volume that occurred in the watershed catchment of Krueng Peusangan. Having viewed the differences and similarities location against variabel temperature, evapotranspiration, moisture, discharge, rainfall for the fivepoint, watershed locations of Krueng Peusangan using Principal Component Analysis (PCA). Based on PCA, the location was selected to analyze the volume of leach discharge measured during 2008-2011 in Wih Nareh and Kr. Teumbo. Absorption volume indicated that occurred instable infiltration at Kr. Teumbo. It needed guidelines for land use arrangement and forest function, especially in the recharge area. So, it could maintain the balance of hydrological cycle, groundwater quantity and quality properly.